2021
DOI: 10.1111/jog.14898
|View full text |Cite
|
Sign up to set email alerts
|

Case of adenomyosis causing the activation of the coagulation system after a complete loss of endometrium following microwave endometrial ablation

Abstract: The formation of microbleed and minute tissue necrosis inside adenomyosis after the shedding of endometrial or endometrial-like tissue within the myometrium during menstruation is receiving attention as a new pathological condition of uterine adenomyosis. These formations might greatly affect coagulation and fibrinolysis function. However, these modulations might occur due to indirect effects of massive hemorrhage from the uterus with adenomyosis. We present a case of adenomyosis in which the patient's coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This indicates that the coagulation system is closely involved in the pathophysiology of established adenomyosis. As evidence, patients with adenomyosis during menstruation may have laboratory abnormalities associated with hypercoagulability and excessive hyperfibrinolysis (10,23). Elevated TAT, SF, D-dimer and PIC levels in patients with adenomyosis reflect a hypercoagulable and hyperfibrinolytic condition (10,23).…”
Section: Mechanisms Underlying the Pathogenesis Of Dic And Thromboemb...mentioning
confidence: 99%
See 4 more Smart Citations
“…This indicates that the coagulation system is closely involved in the pathophysiology of established adenomyosis. As evidence, patients with adenomyosis during menstruation may have laboratory abnormalities associated with hypercoagulability and excessive hyperfibrinolysis (10,23). Elevated TAT, SF, D-dimer and PIC levels in patients with adenomyosis reflect a hypercoagulable and hyperfibrinolytic condition (10,23).…”
Section: Mechanisms Underlying the Pathogenesis Of Dic And Thromboemb...mentioning
confidence: 99%
“…Some patients with adenomyosis with a history of cerebral infarction or pulmonary thromboembolism have been shown to have elevated levels of plasma TAT, SF, D-dimer and PIC, suggesting an increased predisposition to thromboembolic events (10). Kimura et al (23) also presented a rare case of adenomyosis causing the activation of the coagulation system following a complete loss of the endometrium following microwave endometrial ablation. The authors of that study suggested that the formation of microhemorrhage within adenomyotic lesions ws associated with elevated serum levels of the TAT complex and SF, reflecting a hypercoagulable state (23).…”
Section: Reviews Of the Literature On Adenomyosis-associated Thromboe...mentioning
confidence: 99%
See 3 more Smart Citations